Fermentation weight loss, fermentation quality, and bacterial community of ensiling of sweet sorghum with lactic acid bacteria at different silo densities - Xu, Haiwen; Wu, Nier; Na, Na; Sun, Lin; Zhao, Yi; Ding, Haijun; Fang, Yongyu; Wang, Tianwei; Xue, Yanlin; Zhong, Jin (Frontiers in Microbiology, 2022)
Sweet sorghum is an important forage in arid and semi-arid climatic regions. This study aimed to reveal the fermentation weight loss (FWL), fermentation quality, and bacterial community of ensiling of sweet sorghum with lactic acid bacteria LAB; (Lactiplantibacillus plantarum and Lentilactobacillus buchneri) at different silo densities. For this study, sweet sorghum was harvested at the first spikelet of inflorescence stage and ensiled without or with LAB (CK or L) in polyethylene laboratory-scale silos (diameter, 20 cm; height, 30 cm) at densities of 650 (CK_650 and L_650), 700 (CK_700 and L_700), and 750 kg/m3 (CK_750 and L_750), respectively. The FWL, fermentation quality, microbial counts, and bacterial community of the silage were assessed after 100 days of ensiling. L_750 had a lower FWL than CK_650, _700, and _750 after 100 days of ensiling (P < 0.005), and the FWL was affected by silo density and inoculating LAB (P < 0.005). All silages had low pH (<4.0) and ammonia nitrogen content (<50 g/kg total nitrogen) and did not contain propionic and butyric acids; moreover, inoculating LAB increased lactic and acetic acids (P < 0.005). Bacterial communities in inoculated and uninoculated silages were clustered together, respectively, and clearly separated from each other. The total abundance of Lactiplantibacillus and Lentilactobacillus in fresh forage was <1%. Lactiplantibacillus had the highest abundance in all silages (from 71.39 to 93.27%), followed by Lentilactobacillus (from 3.59 to 27.63%). Inoculating LAB increased the abundance of Lentilactobacillus in each silo density (P < 0.005) and decreased Lactiplantibacillus in the silage in densities of 700 and 750 kg/m3 (P < 0.005); moreover, increasing silo density decreased Lactiplantibacillus abundance and increased Lentilactobacillus abundance in inoculated silages (P < 0.005). Overall, sweet sorghum silage showed satisfactory fermentation quality, with a density of no <650 kg/m3, and inoculating LAB improved fermentation quality and reduced FWL. Lactiplantibacillus and Lentilactobacillus presented as minor taxa in fresh sweet sorghum and dominated the bacterial community of all silages. Inoculating LAB was the main factor affecting the bacterial community of sweet sorghum silage. Moreover, inoculating LAB and increasing silo density can contribute to the decreasing Lactiplantibacillus abundance and increasing Lentilactobacillus abundance.